Nosocomial infection by Klebsiella pneumoniae among neonates: a molecular epidemiological study. (February 2021) - Luo, K.; Tang, J.; Qu, Y.; Yang, X.; Zhang, L.; Chen, Z.; Kuang, L.; Su, M.; Mu, D.
Summary: Background: Nosocomial infection by Klebsiella pneumoniae (Kp) and drug resistance of Kp among neonates is a major concern. Hypervirulent K. pneumoniae (hvKp) infections are gradually increasing worldwide. Carbapenem-resistant hvKp infection has brought challenges to clinical treatment. Aim: To evaluate the changes in drug resistance trends of Kp strains in neonatal intensive care unit (NICU) nosocomial infections, to analyse drug resistance genes and virulence genes of carbapenem-resistant K. pneumoniae (CRKP) and to identify whether these CRKP strains are hvKp. Methods: A total of 80 neonates with Kp nosocomial infections from 2013 to 2018 were retrospectively studied. Drug susceptibility testing was performed on 80 Kp strains, among which the 12 CRKP strains were further studied. Findings: Kp accounted for 26.9% of nosocomial infections in the NICU. CRKP strains accounted for 15.0%. Among the 80 nosocomial infection Kp strains, CRKP strains accounted for 33.3% and 53.3% in 2017 and 2018 respectively. One of the 12 CRKP strains was positive in the drawing test. The 12 CRKP strains were divided into four complete genome sequence types: cgST1 ( N  = 2), cgST2 ( N  = 1), cgST3 ( N  = 1), and cgST4 ( N  = 8). Among genes that mediated carbapenem resistance, strains of cgST4 carried NDM-5, strains of cgST2 and cgST3 carried NDM-1, and strains of cgST1 carried IMP-4. None of the 12 CRKP strains carried rmpA/rmpA2 (highly related with hvKp). Conclusion: Nosocomial infections of CRKP among neonates are becoming common, but no hvKp was found among the CRKP strains in this study.